Analysis and Evaluation of Quality Indicators and Volatile Compounds of Different Rice Cultivars with Geographical Indication - WANG Qin, ZHOU Changyan, ZHAO Xiaoyan, LI Xiaobei, LI Xujiao, JIANG Zhenghui, ZHANG Yanmei (Shipin Kexue)
In order to investigate the differences in the quality of different rice cultivars with geographical indication (GI), 9 GI rice landraces were analyzed for 18 quality indicators including appearance, nutritional quality, cooking and eating quality, and volatile compounds. Using headspace solid-phase microextraction (HS-SPME) combined with gas chromatography-mass spectrometry (GC-MS) followed by odor activity value (OAV) analysis, the major odor-active compounds of rice were identified as 2-acetyl-1-pyrroline, hexanal, heptanal, octanal, nonanal, trans-2-octenal, hexanol, 1-octen-3-ol, and heptanol. A total of 42 differential volatile compounds were detected in GI rice from Northeast China versus other regions in the country using multivariate statistical analysis, including 25 hydrocarbons and 17 volatile aroma compounds such as alcohols, ketones, aldehydes, and esters. The results of correlation analysis showed that the protein content was significantly negatively correlated with the amylose content and the taste value, and the amylose content was significantly related to the gelatinization properties of rice starch. The protein content had an extremely significantly negative correlation with the aldehyde content and a significantly positive correlation with the hydrocarbon content. Cluster analysis divided the nine GI rice varieties into three categories. The first category consisted of five varieties to Northeast China, characterized by low chalky grain rate and protein conetent, high amylose content, low pasting temperature, firm and elastic texture, and high proportions of aldehydes, alcohols and ketones. The second category included Yuanyang rice and Xiaozhan rice, characterized by moderate pasting temperature and amylose content and the highest levels of total volatile compounds (627.7 μg/kg) and hydrocarbons (269.6 μg/kg). The third category comprised rice varieties from Sheyang and Chongming in South China, characterized by low amylose content, high viscosity, high pasting temperature, soft and sticky texture, and medium levels of hydrocarbons (159.4 μg/kg). This study could provide the basis for the quality evaluation of different GI rice culvars.